Shape Shifting: Toward a Theory of Racial Change - Paul Spickard (Genealogy, 2022)
We are accustomed to thinking of identities—racial, ethnic, often religious—as if they were permanent, unalterable features of individuals and groups. The theory enunciated here is directed to illumine individuals and groups whose lives are more complicated than that. Such people are shape shifters. At different times in their lives, or over generations in their families and communities, their identities have changed from one group to another. This article sets out an agenda for understanding the phenomenon of racial or other primary identity change. It seeks to understand what kinds of circumstances produce racial change, what sorts of people and groups are likely to change identities, what processes facilitate identity change, and what kinds of work that change is doing. It describes three major intertwined processes at work. Sometimes it is mainly a matter of changes in context and the menu of identities that are available. Sometimes changes in identity are imposed by governments, by institutions, or by society at large. And sometimes it is an individual’s, a family’s, or an entire ethnic group’s choice to make a change. The complexity and contingency of these processes may tend to diminish our commitment to the very idea of social inquiry as science.